Genetic variability in the cholecystokinin A receptor affects lipid profile and glucose tolerance in patients with polycystic ovary syndrome - Eva Drnovsek; Mojca Jensterle; Katja Goričar; Sara Redenšek; Andrej Janež; Irina Milisav; Vita Dolžan (Archives of Medical Science)
Introduction Cholecystokinin (CCK) is involved in several metabolic pathways, and CCK agonists are considered as a potential novel treatment option in populations with increased metabolic risk, including polycystic ovary syndrome (PCOS). As genetic variability of cholecystokinin A and B receptor genes (CCKAR and CCKBR, respectively) may modify their biological actions, we investigated the impact of CCKAR and CCKBR genetic variability on anthropometric and metabolic parameters in patients with PCOS.